PEMANTAUAN SURVEILANS PROGRAM MALARIA DALAM MEMPERTAHANKAN SERTIFIKASI ELIMINASI DI KABUPATEN ROKAN HULU - Rahmat Saputra; Agus Alamsyah; Yeni Devita (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2020)
Malaria surveilance is a systematic and continuous analysis activity and influencing factors of the malaria disease. In july 2017 an outbreak occured at hamlet bungo, village sialang jaya, subdistrict rambah Rokan Hulu district with positive cases 40 patients. The purpose of this study is to monitor the surveillance of malaria program on maintaining the elimination license in Rokan Hulu region of 2018. Qualitative method is used in this research with exploratory design and phenomenology approach. The study was conducted in Rokan Hulu District of Health Office on February 2018. The informan were 4 persons. The result in the input found that there are no entomologists in Rokan Hulu Regency as standard determined by Directorate General of P2P. The training process obtained by malaria program managers is very low, less active case detection and the integrated cross-sector and cross program surveillance hasn’t yet running. In the output, monthly case report of all public health service is incomplete. Many much deficiencies in the input, process, and output points has resulted in inadequate implementation of surveillance activities in Rokan Hulu District. Parties in the Public Health Office should request entomologist submission, conduct training related to malaria surveillance, increase active case detection and the integrated cross-sector and cross program surveillance running and emphasize more to the malaria officers at public health service to submit reports every month for on maintaining elimination license in rokan hulu region.